2000
DOI: 10.1021/cm000227t
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Curing Behaviors of Phenolic Resin-Layered Silicate Nanocomposites Prepared by Melt Intercalation

Abstract: The melt intercalation and curing behavior of phenolic resin (P1) were investigated by use of layered silicates, such as pristine montmorillonite (PM), dodecylammonium-modified montmorillonite (C12M), octadecylammonium-modified montmorillonite (C18M), benzyldimethyloctadecylammonium-modified fluorohectorite (C18BH), and hexamethylenetetramine (HMTA), as curing agents. It was found by X-ray diffraction that the uncured phenolic resin was intercalated into PM, C18M, and C18BH. Cured phenolic resin-layered silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 47 publications
2
74
1
1
Order By: Relevance
“…Therefore, a limited number of attempts have been made to understand layered silicates in PF resins. Early studies on organoclay reinforced linear novolac PF resin nanocomposite demonstrated that the structural affinities between the clay modifier and the polymer enhance intercalation (Choi et al, 2000;. The same research group also reported an ideal silicate concentration of 3% which greatly improved tensile strength, tensile modulus, toughness, and elongation-at-break (Byun et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, a limited number of attempts have been made to understand layered silicates in PF resins. Early studies on organoclay reinforced linear novolac PF resin nanocomposite demonstrated that the structural affinities between the clay modifier and the polymer enhance intercalation (Choi et al, 2000;. The same research group also reported an ideal silicate concentration of 3% which greatly improved tensile strength, tensile modulus, toughness, and elongation-at-break (Byun et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…It also plays an important role as an anti-microbial agent and important precursor to many other chemical compounds. The synthesis of formaldehyde-based polymers bearing N, O, S and P donor groups has been an active field of research because of their ablative properties in modeling compounds, the wood industry, in coatings, composite materials [11,12] and in manufacture of automobiles, and used to make components for the transmission, electrical system, engine block, door panels, axles and brake shoes.…”
Section: Introductionmentioning
confidence: 99%
“…[10] To solve this problem, Usuki et al [11] attempted to synthesize phenolic resin/layered silicate nanocomposites by an intercalative polymerization approach, employing phenol and formaldehyde and a modified montmorillonite. Lee et al, [10] as well as, Choi et al [12]- [13] synthesized phenolic resin/layered silicate nanocomposites by melt intercalation of a linear novolac. Currently, only fairly limited researches on resol type phenolic resin layered silicate nanocompositesvia in situ polymerization of monomers -have been published.…”
Section: Introductionmentioning
confidence: 99%